Pulmonary hamartoma: a clinic-pathologic study of 206 consecutive cases focusing on different histologic variants - MelocchiLaura; CavazzaAlberto; SirolliMaria; AlbertiniElisa; MelottiSofia; BizzarroTommaso; ObertiArianna; DavoliFabio; RossiGiulio (中华胸部外科电子杂志; 卷 9, 编号 3 (August 2022): 中华胸部外科电子杂志, 2022)
Background: Pulmonary hamartoma (PH) is the most common benign pulmonary tumor usually presenting as a solitary, well-demarcated nodule composed of mature cartilage and adipose tissue. Some unusual histologic variants are challenging on clinic-radiologic and pathologic examination. Methods: We collected a multicentric, retrospective, consecutive series of 206 PH with clinical characteristics and histologic variants. Results: Clinical data were in line with the literature demonstrating a male prevalence (2:1) and a median age of 61.6 years. The median size of the nodule was 17.8 mm. When performed, SUVmax >2.5 at FDC-PET was evidenced in 4% of cases (5 out of 119) and was significantly associated with undifferentiated/myxoid histology. Conventional histology showing chondroid or chondro-lipomatous PH was quoted in 186 cases (90%), while leiomyomatous and undifferentiated/myxoid variants were recorded in 20 cases (10%). The high rate of unusual variants on pathology is possibly related to a selection bias due to external consultations or surgical excision of the lesions lacking classic features at imaging studies. Conclusions: About 10% of PH may show unusual histology and SUVmax >2.5 at FDC-PET in 4%. These uncommon findings may challenge the correct recognition, raising some concerns in terms of differential diagnosis with several other mesenchymal tumors in the lung. These features should be kept in mind to achieve a correct diagnosis and avoid unnecessary invasive treatments.